Urinary Incontinence and Related Quality of Life Among Elderly Men - Tufail Hussain Tahir, Saad Aziz, Misbah Jan, Hafiz Muhammad Aman Ashraf, Yasir Sadiq, Hasnat Shabbir, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction:Urinary Incontinence (UI)the complaint of any involuntary leakage of urine-is common in women that increases with age and may decrease quality of life Objective:The main objective of the study is to find the urinary incontinence (UI) and related quality of life among elderly men.Material and methods: This cross-sectional study was conducted at Urology Poonch Medical College Rawalakot Azad KashmirDuring May to September 2021. The study included 109 elderly patients aged 65 years and older. Informed consent was obtained from all patients and the study protocol was approved by the local ethics committee of our institution. The patients were assessed sequentially based on their presentation to the physical medicine and rehabilitation outpatient clinic Results: The study included 109 elderly patients and mean age of patients was 73.98 ± 7.88 years. Of the study group, 40.4% had UI and 59.6% did not have UI. The difference between the two groups with respect to mean age was not statistically significant (p = 0.093). Practical implication: UI is coomon among older men so this study will helps us to improve the quality of life. Conclusion: It is concluded that UI is common among older men and is associated with worse QoL. Health care professionals should discuss UI with older men. Keywords: Quality of life, UI, Health care, WHO, Individuals, Population,